Total relaxation as a mindfulness and concentration technique for students at Ekayana Dharma Budhi Bhakti junior high school - Aryo Sentana; Hendri Ardianto; Sutiyono Sutiyono (International Journal of Science and Applied Science: Conference Series, 2025)
This study aims to identify the effect of total relaxation techniques as part of mindfulness on the learning concentration of students at Ekayana Dharma Budhi Bhakti Junior High School. The main problems faced by students include difficulty in maintaining concentration while studying, academic stress, social pressure, and an unsupportive learning environment. Most students do not yet have effective strategies or techniques for managing stress and improving their focus on learning. This study uses a quantitative approach with a survey method. The population consists of 109 students, and 31 students were sampled using the Proportional Random Sampling technique. Data collection was carried out using a closed questionnaire with a Likert scale that had been tested for validity and reliability. The data analysis technique used simple linear regression with the help of SPSS version 26 software. The results showed that there was a positive and significant effect between total relaxation as a mindfulness technique and students' learning concentration, with a t-value of 7.698 and significance (p) of 0.000 (p < 0.05). The coefficient of determination (R²) value of 0.438 indicates that the total relaxation technique contributes 43.8% to the increase in students' learning concentration, while 56.2% is influenced by other factors outside this study. These findings indicate that the integration of mindfulness techniques, particularly total relaxation, is effective in improving student learning focus and is recommended to be systematically implemented in educational practices at the junior high school level.